Oral History Interview: Jim Martin (1464) - Martin, Jim (My University, 2017)
In his 2016 interview with Greg Bond, Judge Jim Martin discusses his life, from a childhood in Racine, Wisconsin to a judgeship in Madison. Martin talks about the experience of segregation, specifically from the vantage of a young, black, student athlete. Later he attended the University of Dubuque, where he was further involved in sports. After Dubuque he taught briefly. Martin discusses later transition into coaching college football at UW-Madison. After coaching for UW, Martin became a student at its law school. After his time in law school Martin Worked in the city attorney's office and later became a judge. Here Martin reflects on race, sports, and his career in law.
Interview by Greg Bond
Keywords: Student Athletes; UW-Madison Law School; Vietnam War; Sterling Hall Bombing; 1970s; National Guard; Wisconsin Intercollegiate Athletics Association (WIAA); Racism; Refereeing; Kemp, Stan; Recruiting; Ritcherson, Les; Hirsch, Elroy; Jardine, John; Coaching; UW-Madison Football; Physical Education; Segregation/Integration; Little League; University of Dubuque; Racine